2015
DOI: 10.1021/acsami.5b05510
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Derived Graphenic Fibers for Capacitive Desalination of Brackish Water

Abstract: We describe a simple and inexpensive cellulose-derived and layer-by-layer stacked carbon fiber network electrode for capacitive deionization (CDI) of brackish water. The microstructure and chemical composition were characterized using spectroscopic and microscopic techniques; electrochemical/electrical performance was evaluated by cyclic voltammetry and 4-probe electrical conductivity and surface area by Brunauer-Emmett-Teller analysis, respectively. The desalination performance was investigated using a labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…The result suggested that the thickness of the EDL was highly correlated with ionic strength. Although the effects of coexisting ions on phosphate adsorption without applied potential followed the order of SO 4 2-> NO 3 -> Cl -, which indicated a great agreement with the conclusion from the study [25], Pugazhenthiran et al [52] implied that the ability of EDL adsorption follows the order of Cl -> NO 3 -> SO 4 2during capacitive deionization. The outer-sphere complexation formed is a dominant action as the adsorption capacity of phosphate decreases with increasing ionic strength [53].…”
Section: Influence Of Initial Solution Ph On Phosphate Removal On Mg-supporting
confidence: 84%
“…The result suggested that the thickness of the EDL was highly correlated with ionic strength. Although the effects of coexisting ions on phosphate adsorption without applied potential followed the order of SO 4 2-> NO 3 -> Cl -, which indicated a great agreement with the conclusion from the study [25], Pugazhenthiran et al [52] implied that the ability of EDL adsorption follows the order of Cl -> NO 3 -> SO 4 2during capacitive deionization. The outer-sphere complexation formed is a dominant action as the adsorption capacity of phosphate decreases with increasing ionic strength [53].…”
Section: Influence Of Initial Solution Ph On Phosphate Removal On Mg-supporting
confidence: 84%
“…Electrospun cellulose‐derived CNFs are promising materials in electrochemical and separation applications . One of the promising applications of cellulose‐based CNFs is anode material for SIB.…”
Section: Activated Carbon Fibers Nanofibers and Mats: Nonstructuralmentioning
confidence: 99%
“…Materials with high electro-adsorption properties have been used to develop capacitive deionization units. 82,83 New technologies using nanostructures have been used to create efficient water harvesters from air. 84 , while new nanocomposite structures with graphene are claimed to be able to reduce desalination costs substantially.…”
Section: The Quest For Clean Watermentioning
confidence: 99%